Retracted: Optimasi Laju Produksi dengan Cara Desain Ulang Progressive Cavity Pump (PCP) pada Sumur “X” Lapangan “Y” - Eko Prastio; Abdullah Rizky Agusman (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2021)
This article has been retracted at the request of publisher.Reason: This article is virtually identical to the previously published article